ASSESSING THE EFFECTIVENESS OF SOLAR PANELS IN URBANIZED AREAS: AN ANALYSIS OF BENEFITS AND CHALLENGES - Амурова Наталья Юрьевна (Web of Journals Publishing, 2024)
The purpose of the article is to analyze the effectiveness of the use of solar panels in the urbanized areas of the city of Tashkent in order to determine their potential in mitigating energy shortages and reducing the negative impact on the environment. The main attention is paid to the assessment of the economic and environmental feasibility of integrating solar energy systems into the urban infrastructure, as well as the identification of challenges and prospects for the development of this area in the context of Tashkent.
Keywords: solar energy, solar panels, urbanized areas, energy deficit, environmental sustainability, energy efficiency, infrastructure optimization, energy saving, innovations.